PRIMARY EPISODE OF BIPOLAR AFFECTIVE DISORDER - Mysula, Yu. I. (International Journal of Medicine and Medical Research, 2020)
Background. Bipolar affective disorder (BAD) is a topical issue of contemporary psychiatry. The features of the primary episode (PE) of the disease are extremely important for prognosis, treatment and rehabilitation measures of BAD. Individual psychological features of the patients with PE of BAD are still unexplored that complicates development of new methods of prediction, treatment and prevention of BAD. Objective. The aim of the study was to investigate individual psychological features of the patients with a primary episode of bipolar affective disorder, taking into account the gender factor and clinical variant of the BAD debut. Methods. 153 patients (65 men and 88 women) with a primary episode of bipolar affective disorder were examined. The patients were divided into three groups according to the clinical variant of the course of PE of BAD: depressive variant, manic variant and mixed variant. The examination was carried out using the Standardized multifactor method of personality research (SMMPR). Statistical processing of the data was performed using the non-parametric Mann-Whitney test. Results. The most significant differences in the quantitative indicators of SMMPR were found when comparing depressive and manic, as well as depressive and mixed variants of PE of BAD, and lesser – when comparing manic and mixed variants. Most of all, these differences were expressed in terms of pessimism, impulsiveness, individualism and optimism. Conclusions. Some peculiar features of male and female patients with depressive, manic and mixed variants of PE of BAD promoting to search for new methods of prediction, treatment and prevention of BAD have been defined.